(3GdJGLs - (3YeQh Hf HMQ Hf eMHhH GdcfGfj HGdhdGA, GddjKj, CHh YKeGf, GdLGMX,J (B255 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dg eG ai GdSehGJ heGai GdCQV hdg GdMeO ai GdBNQI GeG HYO aEf GdPi OYGfG Edi EfTC cJGHfG gPG eYGf s
(3BNQgG (B:s
(3abGd YHO Gddg jG CejQ GdeDefjf HhGOQ GdNGWQ hCZaGd GdeTGjN bGd dg (B: (3UObJ , NP ai ZjQgG Je GdLRA jJdhg PcQ GdeOGFf Cf YjSi Hf ehSi s
(3LRA efgs
(3HChdgG JMHjS ef GdSdWGf CHj GdYHGS CMeO GdeQjfi Ydi NRGfI LGeY GdCfOdS HaGS SfI (B792s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B74 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B7s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(40 / 654) s
Keywords: (3GdCOHs